2006
DOI: 10.1111/j.1574-6968.2006.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania donovanicyclin 1 (LdCyc1) forms a complex with cell cycle kinase subunit CRK3 (LdCRK3) and is possibly involved in S-phase-related activities

Abstract: Expression of Leishmania donovani cyclin 1 (LdCyc1) mRNA during the cell cycle of promastigotes is S-phase specific. Here, we show that the LdCyc1 protein is periodically expressed and the activity of its associated kinase varies during the cell cycle in line with its expression pattern. In addition, we have shown that LdCRK3, homologous to CRK3 from L. mexicana, is the cognate Cdk partner of LdCyc1 and that the activity of the complex is inhibited specifically by heat stable factor(s) from the parasite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
1
19
0
2
Order By: Relevance
“…The mRNA of S-phase cyclin LdCyc1 of L. donovani was found to contain a single copy of the conserved octamer sequence in its 5 0 -UTR [13,14], and in the present study, RNA electrophoretic mobility shift assay (REMSA) was performed to determine whether LdCSBP interacts with the UTR specifically. The slower moving bands in REMSA with the extract of Sf9 insect cell expressing LdCSBP and a 32 P-labeled RNA probe containing the 5 0 -UTR of LdCyc1 (Fig.…”
Section: Ldcsbp Interacts Specifically With Utr Of An S-phase Mrna Thmentioning
confidence: 94%
“…The mRNA of S-phase cyclin LdCyc1 of L. donovani was found to contain a single copy of the conserved octamer sequence in its 5 0 -UTR [13,14], and in the present study, RNA electrophoretic mobility shift assay (REMSA) was performed to determine whether LdCSBP interacts with the UTR specifically. The slower moving bands in REMSA with the extract of Sf9 insect cell expressing LdCSBP and a 32 P-labeled RNA probe containing the 5 0 -UTR of LdCyc1 (Fig.…”
Section: Ldcsbp Interacts Specifically With Utr Of An S-phase Mrna Thmentioning
confidence: 94%
“…Trypanosomatid CDKs contain cyclin-binding regions as anticipated (Naula et al 2005 ), whereas the presence of a cyclin (CYC2, CYC3, CYC6 for T . brucei , and CYC1, CYCA and CYC6 for Leishmania ) for the activity of the trypanosomatid homologue of mammalian CDK1 (CRK3) has been shown (Wang et al 1998 ;Van Hellemond et al 2000 ;Li and Wang 2003 ;Hammarton et al 2003Hammarton et al , 2004Tu and Wang 2004 ;Banerjee et al 2006 ;Gomes et al 2010 ). The function of two kinases from L .…”
Section: Kinasesmentioning
confidence: 99%
“…The purified proteins could also be phosphorylated in a Cy-motif dependent manner by LdCyc1 associated kinase (Fig. 2C) isolated from L. donovani promastigote extract through anti-LdCyc1 immunoprecipitation [10], suggesting the proteins could be the authentic in vivo substrates.…”
Section: The In Vitro Expressed Proteins Act As Substrates Of Ldcyc1/mentioning
confidence: 99%
“…It was also observed that the specificity of Clb5-Cdc28 of budding yeast in S-phase primarily depends on the substrate RXL motif [14]. Therefore, in order to identify the potential substrates of S-phase cell cycle kinase LdCyc1/CRK3 from Leishmania [9,10], 28 putative ORFs containing both the conserved Cy-motif and the Cdk phosphorylation site were selected from the genome database of L. major for screening. The ORFs which were larger than 3 kb in length and/or A B contained putative trans-membrane domain were not included in the present studies to avoid the difficulties of amplification of large templates from the GC-rich genome and insolubility of the expressed proteins, respectively.…”
Section: Three Proteins Containing Both Cy-motif and Cdk Phosphorylatmentioning
confidence: 99%
See 1 more Smart Citation